(untitled) (Gaceta Técnica, 2014)
The process of technological change that occurred in recent decades began deep movements in global society, approaching human groups regardless of physical distance and crumbling social behavior, until yesterday petrified to change. This generated economic and social movements, triggering expectations of better living conditions, with consequent pressure on governments and society itself. Education as a basic structure of production of information and knowledge is not without it. The University Centroccidental aware of the above, designed and approved policies and standards to strengthen new forms of teaching and learning blended learning, which may contribute to increased institutional efficiency in the medium term. The digitization of the activities of teaching, research and extension will contribute to an enhancement of new forms of financing to support the new costs attributable to the implementation of new technology platforms